Factors Effect on Corporate Cash Holdings of the Energy Enterprises Listed on Vietnam's Stock Market - Thu, Phung Anh; Khuong, Nguyen Vinh (International Journal of Energy Economics and Policy, 2018)
This study examines the factors effect on corporate cash holdings of the energy enterprises listed on Vietnam's stock market. Our data set includes 28 energy companies on Vietnam stock markets (HNX and HOSE) in the period from 2010 to 2016, with a total of 196 firm-year observations being collected. We used GMM estimator to test our hypotheses. The results show a negative association between leverage, return on assets, operating cash flow and corporate cash holdings while a tangible asset has a positive relationship. Keywords: corporate cash holdings, energy enterprises, Vietnam. JEL Classifications: G33 G31